Erythropoietin combined with ACE inhibitor prevents heart remodeling in 5/6 nephrectomized rats independently of blood pressure and kidney function - Koleganova, Nadezda; Aldebssi, Firas; Schäfer, Sebastian Markus; Bekeredjian, Raffi; Schirmacher, Peter; Ritz, Eberhard; Groß-Weissmann, Marie-Luise (American journal of nephrology, 2013)
Cardiovascular disease is the primary cause of mortality in patients with chronic kidney disease (CKD). Heart remodeling in CKD comprises mainly interstitial fibrosis and capillary loss. Beyond correcting renal anemia, erythropoietin (Epo) has potentially beneficial pleiotropic effects on heart remodeling. Methods: 12-week-old male Sprague-Dawley rats were randomized to 5/6 nephrectomy (NX) or sham operation (sham-op); subsequently, they received murine Epo (2.5 μg/kg/week), enalapril (12 mg/kg/day), Epo + enalapril, Epo + dihydralazine (25 mg/kg/day), or vehicle. Heart function and morphology was assessed after 16 weeks of treatment. Results: Compared with sham-op (81.2%), left ventricle fractional shortening was reduced in vehicle-treated NX (66.3%) and this was ameliorated by Epo (72.6%) and even prevented by enalapril (80.6%). Capillary length density was lower and the area of fibrosis more marked in vehicle-treated NX compared to sham-op. Capillary rarefaction and heart fibrosis were prevented in NX treated with Epo + enalapril and reduced in NX treated with enalapril and Epo + dihydralazine. Despite higher blood pressure, treatment with Epo reduced heart fibrosis but failed to prevent capillary loss. In parallel, expression of the p47phox NADPH oxidase was higher in untreated NX and was effectively reduced in NX treated with Epo + enalapril. Under basal conditions there was no difference between the groups regarding myocardial hypoxia as reflected by pimonidazole staining. Conclusion: Epo in combination with enalapril caused additive reduction of cardiac fibrosis and microvessel disease in 5/6 nephrectomized rats presumably by decreasing myocardial oxidative stress.
Gesehen am 10.02.2021